Assessing the overall benefit of a medication: cumulative benefit of secukinumab over time in patients with moderate-to-severe plaque psoriasis. (3rd April 2017) - Armstrong, April W.; Feldman, Steven R.; Korman, Neil J.; Meng, Xiangyi; Guana, Adriana; Nyirady, Judit; Herrera, Vivian; Zhao, Yang
Abstract: Background: Conventional measurements for assessing psoriasis treatment effects capture improvements at fixed, pre-specified timepoints, failing to account for cumulative clinical benefit over time. Objective: Explore the innovative concept of "cumulative clinical benefit" by examining the effect of secukinumab over 52 weeks in moderate-to-severe psoriasis patients. Methods: Cumulative clinical benefit was determined as the area-under-the-curve of the percentage of responders over 52 weeks (AUC0–52 wks ), using pooled data from two phase III trials for patients receiving secukinumab (300 or 150 mg) or etanercept. Results: Normalized cumulative benefit with secukinumab 300 mg, secukinumab 150 mg, and etanercept was 74.2%, 63.2%, and 50.5%, respectively, for PASI 75; 58.0%, 42.5%, and 29.5%, respectively, for PASI 90; 32.3%, 18.8%, and 8.7%, respectively, for PASI 100; and 58.3%, 47.9%, and 38.3%, respectively, for DLQI 0/1. 52-week PASI 75 clinical benefit ratios for secukinumab 300 and 150 mg versus etanercept were 1.47 and 1.25, respectively; the ratio of the two secukinumab doses was 1.17, favoring 300 mg. Limitations: Post hoc analysis. Conclusion: Cumulative clinical benefit estimated by AUC0-52 wks is a novel measure for comparing psoriasis treatments. Secukinumab 300 mg provides greater cumulative clinical benefit than secukinumab 150 mg; both provide greater cumulative benefit than etanercept.